Co-creating a vision for the production system of La Montañita 20 years from now: A territory of food, biodiversity and hope - Lopez, María Claudia; Rodríguez, Luz A.; Correal, Antonia (2024)
The development of bioeconomy alternatives in Caquetá offers the possibility to transform a territory currently dominated by pastures into places where forests used to stand and demonstrate the value of local identities and “campesino” livelihoods in the Amazon. Developing bioeconomies in this Colombian region implies reducing or eliminating deforestation, recovering soils and degraded ecosystems, diversifying products and adding value to Amazonian products, implementing sustainable practices in productive systems, strengthening of traditional Amazonian practices and equitable sharing benefits, and promoting women’s empowerment and integrating the youth into decision-making. In order to co-create a vision for the territory that holds these characteristics, in October 31st and November 1st, 2024, we held a workshop in the facilities of Agrosolidaria La Montañita, our local partners; men, women and young people were intentionally invited.